A health economic model for the development and evaluation of innovations in aged care: an application to consumer-directed care—study protocol. Issue 6 (25th June 2014) - Ratcliffe, Julie; Lancsar, Emily; Luszcz, Mary; Crotty, Maria; Gray, Len; Paterson, Jan; Cameron, Ian D
Abstract : Introduction: Consumer-directed care is currently being embraced within Australia and internationally as a means of promoting autonomy and choice in the delivery of health and aged care services. Despite its wide proliferation little research has been conducted to date to assess the views and preferences of older people for consumer-directed care or to assess the costs and benefits of such an approach relative to existing models of service delivery. Methods and analysis: A comprehensive health economic model will be developed and applied to the evolution, implementation and evaluation of consumer-directed care in an Australian community aged care setting. A mixed methods approach comprising qualitative interviews and a discrete choice experiment will determine the attitudes and preferences of older people and their informal carers for consumer-directed care. The results of the qualitative interviews and the discrete choice experiment will inform the introduction of a new consumer-directed care innovation in service delivery. The cost-effectiveness of consumer-directed care will be evaluated by comparing incremental changes in resource use, costs and health and quality of life outcomes relative to traditional services. The discrete choice experiment will be repeated at the end of the implementation period to determine the extent to which attitudes and preferences change as a consequence of experience of consumer-directed care. The proposed framework will have wide applicability in the future development and economic evaluation of new innovations across the health and aged care sectors. Ethics and dissemination: The study is approved by Flinders University Social and Behavioural Research Ethics Committee (Project No. 6114/SBREC). Findings from the qualitative interviews, discrete choice experiments and the economic evaluation will be reported at a workshop of stakeholders to be held in 2015 and will be documented in reports and in peer reviewed journal articles.